Comparative Analysis and Functional Mapping of SACS Mutations Reveal Novel Insights into Sacsin Repeated Architecture. Issue 3 (18th February 2013) - Romano, Alessandro; Tessa, Alessandra; Barca, Amilcare; Fattori, Fabiana; Fulvia de Leva, Maria; Terracciano, Alessandra; Storelli, Carlo; Santorelli, Filippo Maria; Verri, Tiziano
<x xml:space="preserve">Abstract</x> ARSACS is a neurological disease with mutations in SACS, encoding sacsin. Three repeated regions (Sacsin Internal RePeaTs) larger than the previously described Sacsin Repeating Region supra‐domains were found in sacsin, organized in sub‐repeats (sr1, sr2, sr3, srX). Comparative analysis of vertebrate sacsins in combination with fine positional mapping of a set of human mutations reveals that the sub‐repeats are functional. The position of the pathogenic mutations in the sub‐repeats appears to be related to the severity of the clinical phenotype. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>